ANALISIS KEPATUHAN WAJIB PAJAK ATAS PAJAK PENGHASILAN (PPh) PASAL 21 TERHADAP GAJI KARYAWAN CV. PUTRA JAYA PERKASA - Simamora, Natan Manogu (EKONOMIA, 2012)
The purpose of this study was to determine compliance with the CV.Putra Jaya Perkasa Samarinda in the calculation, deposit, and reporting of Income Tax Article 21 of the salary of employees according to the Taxation Law applies.The analytical tool used to test the truth of the hypothesis are : 1) by using the Rule Of Law of the Republic of Indonesia No. Tax 28 Year 2007 concerning General Provisions and Taxation Procedures and No. 36 of 2008 on Income Tax, and 2) Calculation of Income Tax Article 21, Deposit CNS, and Reporting SPT. Based on the result of the study authors obtained the result of analysis of that calculation, deposit, an reporting of Income Tax (Income Tax) of Article 21 are conducted by the CV. Putra Jaya Perkasa Samarinda different from the calculation, depositing, and reportingof Income Tax, Article 21 According to the Taxation law applies.Based on the analysis result can be concluded that the calculations, depositing, and reporting of Income Tax of article 21 in January to December of 2011 conducted by the CV. Putra Jaya Perkasa Samarinda has not fully complied with and implemented in accordance with the Act Taxation laws in force and thus the hypothesis can be accepted.